Implementation of the Utilization of West Lampung Traditional Cultural Expression in the Legal System Perspective of Intellectual Property - Erlina B.; Zainab Ompu Jainah; Melisa Safitri; Intan Nurina Seftiniara (Global Writing Academica Researching & Publishing, 2022)
The embodiment of West Lampung Traditional Cultural Expressions has not been optimal both in terms of intellectual property protection and in terms of its usefulness for the local community of West Lampung. In this article, we will discuss how intellectual property legal protection is implemented if it is implemented in the protection of traditional cultural expressions and how far has the West Lampung Regency Government tried to protect and utilize the potential of traditional cultural expressions. This article aims to identify a model of protection against traditional cultural expressions in West Lampung by using normative and empirical legal research methodologies. The results of the discussion show that the Protection of Traditional Cultural Expressions is carried out based on Law Number 28 of 2014 concerning Copyright, Law Number 5 of 2017 concerning the Advancement of Culture, Law Number 11 of 2010 concerning Cultural Conservation and Government Regulation Number 6 of 2017. 2015 concerning Museums, and Regulation of the Minister of Culture Number 106 concerning Indonesian Intangible Cultural Heritage in addition to the autonomy of the Regional Government of West Lampung Regency has also made efforts to preserve istiadar custom through the Regional Regulation of West Lampung Regency Number 14 of 2000 concerning the Guidance, Preservation, and Development of Indigenous Peoples. and Customary Institutions. The West Lampung Regency Government also seeks to protect and preserve traditional cultural expressions by participating in activities such as traditional festivals organized by the Lampung Provincial Government so that the existence of traditional cultural expressions in West Lampung Regency is known to the public. However, overall the protection of the majority of traditional cultural expressions has not been inventoried and utilized optimally, including the traditional cultural expressions of West Lampung. There should be immediate efforts to regulate the protection of traditional cultural expressions in a sui generis manner apart from the Copyright Law.